Solar auto irrigation control (SAIC) using resistivity measurement at multiple points - K. Singh, V; Saxena, Anurag; Kumar Gupta, Ritik; Verma, Nidhi; Kushwaha, Taruna; Soo Chae, Gyoo; Sharma, Ashis; Kumar Bhoi, Akash (International Journal of Engineering and Technology, 2018)
In this article, a special type of microcontroller named as Arduino Nano 3.0 (ATMega 328) is used for the operation of an automatic irriga-tion system which is powered by solar energy. Here, the resistivity of soil is measured with the use of electrode (resistivity sensor). Through this type of irrigation system the farmer can use automatic â€˜ONâ€™ and â€˜OFFâ€™ system for water pump for irrigation. A complete hardware implementation is also presented in this paper. Â